INFRAESTRUTURA VERDE APLICADA À DRENAGEM URBANA - Benini, Sandra Medina; Rosin, Jeane Aparecida Rombi de Godoy (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This text emphasizes the importance of the green infrastructure, as a sustainable practice to subsidize the elaboration of Urban Drainage Plans. For this, a new look was proposed on the urban green, through theoretical and practical subsidies, in which the possibility of optimization of these spaces was demonstrated, through conjugated ecological processes (green and blue system), which are materialized through different typologies of green infrastructure. As a methodological procedure, a qualitative research on the green infrastructure was adopted, taking as a space the city of Tupã / SP. Thus, in carrying out the proposed case study, the research verified the importance of the incorporation of the green infrastructure in the process of urban planning and management, using the city of Tupã. The numerous environmental benefits that contributed significantly, not only to mitigation of the various effects resulting from the urbanization process, but as a primary strategy to ensure environmental quality in urban spaces.